Rural Democracy in China - He, B. author. aut Link
XII, 277 p.
Keywords: This book examines village democracy and the prospects of China's democratization. It explains how three key factors - township, economy and kinship - shape village democracy and account for rural variations. It considers the extension of village to township elections, the idea of a mixed regime and its impact on political development in China.